The teachers and their "place" for high school students. Findings from research on academic paths of school success - Dolo Molina Galvañ; Nieves Blanco; Soledad García (Universidade Federal de Santa Maria, 2013)
Several studies about school success confirm that a positive teacherstudent relationship can favor a strong engagement to school life. Such studies emphasize the fact that teachers contribute to school success when they combine both a demanding and a supportive attitude towards their students, such attitude arising from a sense of value and trust in their students' capabilities. This paper examines the different meaning that successful secondary education students give to their academic experience and defines some of the specific features of teaching which help to create a positive school-student relationship.